El trazo del horizonte - Arango González, Alfonso (Bogotá : Universidad de los Andes, Facultad de Arquitectura y Diseño, Departamento de Arquitectura : Ediciones Uniandes, 2018)
The book explores the way in which five contemporary architects (Alberto Campo Baeza, Sverre Fehn, Peter Zumthor, Frank Gehry, Peter Eisenman) have conceived and represented that elusive line, as if compiling the cosmogonic stories of five distant cultures on the sky and the earth, and their translation in the built space. The presence or absence of the outline of the horizon in the architectural sketches gives clues as to how these architects approach, through drawing, architecture and their relationship with the world understood between the sky and the earth. This book also illustrates, in order to broaden the panorama, how five cultures-scattered throughout time and geography-have conceived and represented the original cosmogonic relationship between heaven and earth, a relationship that has shaped their thought, its customs and its architectures.
y antes fue el gesto / Fabio Restrepo -- Nota previa -- Presentación -- La ambigüedad de la línea -- Parte 1. El horizonte y el dibujo -- Grafía -- Luz y gravedad -- Horizonte arquitectónico -- Materia dibujada -- Dibujos ingrávidos -- Arquificción -- Parte 2. El horizonte y el cosmos -- Mito, canto y trazo -- Cosmogonía mesopotámica -- Arquitectura mesopotámica -- Cosmogonía dogón -- Arquitectura dogón -- Cosmogonía china -- Arquitectura china -- Cosmogonía huitoto -- Arquitectura huitoto -- Cosmogonía griega -- Arquitectura griega -- Conclusiones -- Aperturas -- La ausencia de la línea -- El dilema de la separación -- Línea, superficie, espacio.
Incluye referencias bibliográficas.
En español.
Descripción basada en metadatos suministrados por el editor y otras fuentes.
Recurso electrónico. Santa Fe, Arg.: elibro, 2021. Disponible vía World Wide Web. El acceso puede estar limitado para las bibliotecas afiliadas a elibro.
Keywords: Architectural drawing -- History; Dibujo arquitectónico -- Historia; Arquitectura -- Filosofía -- Historia -- Siglo XX; Architecture -- Philosophy -- History -- 20th century; Libros electrónicos.